Analiza wybranych cech jodły pospolitej (Abies alba Mill.) na powierzchni proweniencyjnej w Rogowie - Szeligowski, Henryk; Bolibok, Leszek; Buraczyk, Włodzimierz; Drozdowski, Stanisław (Leśne Prace Badawcze, 2011)
The paper presents demographic data from a provenance trial of silver fir in Rogów Forest District, central Poland that were monitored when aged 30 and 35 years old. Six silver fir provenances were compared from different regions of its natural range, including five from Poland (Goszcz, Nieskurzów, Stary Sącz, Świętokrzyski National Park, Kobiele Wielkie) and one from Germany (Schwarzwald). Survival and growth parameters (height and DBH) were recorded to assess the vitality and relative breeding value of the fir provenances. Survival was highest in the populations of firs from the Świętokrzyskie Mountains and Schwarzwald, but lowest in the Kobiele Wielkie and Goszcz provenances. The average tree height aged 30 over all of the provenances measured ranged from 5.4 m to 7.8 m. In 2008 (i.e. aged 35), the Kobiele Wielkie population had the tallest mean tree height of 9.9 m, and the smallest population, at 7.4 m, was Schwarzwald. During the five-year measurement period (2003–2008) the firs from the Nieskurzów and Goszcz provenances grew most in height. The provenance Schwarzwald had the smallest mean DBH at both age 30 and 35, whereas the provenance Kobiele Wielkie had the highest DBH. The average increase in trunk diameter during the five-year measurement period was 20.6 mm for all provenances, whereas the diameter growth of provenances Schwarzwald, ŚPN, and Stary Sącz, fell below this value. The fir populations studied significantly differed in their overall height and DBH and in the growth rates (over 5 years) of these two parameters. Firs from Nieskurzów and Schwarzwald were in good condition while the firs from Kobiele Wielkie and ŚPN showed signs of reduced assimilation capacity and needle discoloration. The tested firs were evaluated according to the breeding value index: Świętokrzyski National Park (very good), Kobiele Wielkie and Goszcz (good), Stary Sącz, Nieskurzów (poor), Schwarzwald (bad). When selecting provenances for planting in the central Poland, firs from Świętokrzyski National Park,whereas those from Schwarzwald should be avoided.